Analysis of Artificial Intelligence (AI) application in sports - Ding, P. (Journal of Physics: Conference Series, 2019)
The proposal of "Internet Plus Sports" initiative signifies that it has become a national will to take forward the research and development (R&D) as well as the application of AI technologies in sports, and it also plays an important strategic role in China`s development towards a sports powerhouse. This paper analyzes the significance of AI application in sportsand the current AI adoption in the Chinese sports sector, putting forward some suggestions on the application of AI technologies to the sporting industry.